Needed Skills of Teaching Writing Expression in Upper Grades at Primary School - Alkahtani, Adel Abdullah; Almehayawi, Tahani Mohammed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the skills of teaching written expression to primary school students. The study relied on the descriptive approach. The study population was among the faculty members who specialize in curricula and teaching Arabic in Saudi universities. The two researchers chose a sample of Arabic language books for the upper grades of the elementary stage, and the researchers prepared a list that included the skills of teaching written expression in the upper grades of the elementary stage, and the research reached identifying the appropriate writing skills teaching in the upper grades of the elementary stage, which consisted of (44) items distributed among Five axes, where the first axis included the skills for teaching content consisting of (11) paragraphs, and the second axis included the skills of teaching the form consisting of (8) paragraphs, and the third axis included the skills of teaching the meaning of (10) paragraphs, and the fourth axis included The skills of teaching discipline consisting of (6) paragraphs, and the fifth axis included the skills of teaching written expression and its relevance to other branches of the Arabic language consisting of (9) paragraphs. It also recommended working towards achieving the skills of teaching written expression for primary school students.
Keywords: Skills; Written Expression and Primary School